Individual Customer’ Attitudes, Buying Behavior and Satisfaction of Mutual Fund Customers: Service Mix and Customer Satisfaction in the Banking Industry (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The banking industry has very high impact upon the performance of the different economic sectors and the quality of people’s life in general. The  banking  industry has  always  been witnessing  continuous  developments  andimprovements. One of the industry aspects, which went, and is still going, through a number of such developments  is  the “Service Mix” in terms of types, quality and range of services to be provided. Importance of this aspect stems from its noticeable impact upon satisfying market needs and enhancing the competitive position of the bank in the market place atthe same time.